Neuronal hyperplasia in clinically diagnosed acute appendicitis: A histopathological study in tertiary care centre - Parmar, Riddhi A; Dixit, Riti P; patel, keval Arvindbhai; Sharma, Bhawana S; Dave, Jigna (Journal of Pathology of Nepal, 2021)
Background: Acute appendicitis is one of the most common general surgical emergencies. Around 20-25% of patients who have an appendectomy done are found not to have acute appendicitis on histopathological examination. There is increasing evidence of the involvement of the enteric nervous system, in the immune regulation and monitoring the inflammatory responses. The present study was done to elucidate if neuronal changes in the appendix could be the cause of clinical acute. Materials and methods: Hospital records of 60 cases who were diagnosed as acute appendicitis clinically and who underwent appendectomy either laparoscopic or open, were reviewed. Histopathological records of these resected appendices submitted to the department of histopathology, GAIMS, G.K. General Hospital Bhuj were reviewed for one year for the presence or absence of acute appendicitis or neuronal hyperplasia. Routine Haematoxylin and Eosin stain and S-100 protein staining was done on all these 60 cases. Results: Out of these 60 specimens of appendices received, histopathological examination revealed neuronal hyperplasia in the submucosa and muscularis layer on all the 60 cases. Grading of neuronal hyperplasia was done in all the cases. Out of these 60 specimens of appendices, histopathological examination revealed 48 cases of histopathologically positive acute appendicitis and 12 cases of histopathologically negative acute appendicitis. Conclusions: Neuronal hyperplasia has an important role in the pathogenesis of appendiceal colic in patients with both histopathologically positive acute appendicitis and histopathologically negative acute appendicitis